Children’s Mental Health in Broken Home Families: A Legal Perspective Based on Law No. 23 of 2002 - Amanda, Sutri Rahayu; Hertasmaldi, Hertasmaldi; Nuraiman, Nuraiman (Samara: Journal of Islamic Law and Family Studies, 2025)
The increasing number of couples experiencing broken homes is caused by various factors, and researchers have observed numerous impacts, particularly on children. One of the most significant consequences of parental divorce is the child’s mental health, which often leads to psychological trauma and hinders personal development. This study focuses on how children's mental health in broken home families is viewed through the lens of Law No. 23 of 2002. Employing a qualitative descriptive method, the research was conducted in Kampung Sungai Liku Pelangai, West Sumatra, Indonesia. Data collection tools included observation, interviews, and documentation. Primary data sources were children who had experienced parental divorce, while secondary sources included community leaders, divorced couples, theses, journals, and books. The findings reveal that the disruption of children's mental health in broken home families in Kampung Sungai Liku Pelangai is caused by several factors: lack of openness between spouses, insufficient attention, domestic violence, infidelity, frequent exposure to inappropriate behavior during parental conflicts, and misalignment of visions and goals in the household. Furthermore, from the perspective of Law No. 23 of 2002, children's mental health issues resulting from broken homes are recognized as traumatic, affecting both psychological well-being and personal growth. To protect children in such cases, the law outlines parental responsibilities post-divorce and legal safeguards for children's mental health, as stated in Articles 13, 77, and 78 of Law No. 23 of 2002 on Child Protection.